Inovasi Pendanaan Dalam Peningkatan Mutu Pendidikan Islam di Indonesia - Mustamar Iqbal Siregar (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
This paper discusses the innovation of funding sources of Islamic education. This idea was born as a response to the lack of funding sources in the management of Islamic education in Indonesia, especially those sourced from the government. So, acceleration of Islamic education quality achievement is slow. Unfortunately again, in the middle of the situation, the managers of Islamic schools are poor innovation, and only rely on conventional sources of funding (from the government). Therefore, this innovative idea is considered to be able to contribute solutively to the effort to open the faucet of new funding in the management of Islamic education toward the achievement of quality. Hope, Islamic schools in Indonesia will be served in the form of free education again quality, the availability of adequate facilities and infrastructure, and refresentatif education facilities.